Inactivated whole influenza virus particle vaccines induce neutralizing antibodies with an increase in immunoglobulin gene subclones of B-lymphocytes in cynomolgus macaques. Issue 30 (26th June 2022) - Shiohara, Masanori; Suzuki, Saori; Shichinohe, Shintaro; Ishigaki, Hirohito; Nakayama, Misako; Nomura, Naoki; Shingai, Masashi; Sekiya, Toshiki; Ohno, Marumi; Iida, Sayaka; Kawai, Naoko; Kawahara, Mamiko; et al.
Highlights: Cynomolgus monkeys were immunized with whole influenza virus particle vaccines. Whole particle vaccines induced high titers of neutralizing antibodies in plasma. Immunoglobulin genes after vaccination was examined by a next-generation sequencing. Whole particle vaccines induced an increase in subclones of B-lymphocytes. Abstract: The All-Japan Influenza Vaccine Study Group has been developing a more effective vaccine than the current split vaccines for seasonal influenza virus infection. In the present study, the efficacy of formalin- and/or β-propiolactone-inactivated whole virus particle vaccines for seasonal influenza was compared to that of the current ether-treated split vaccines in a nonhuman primate model. The monovalent whole virus particle vaccines or split vaccines of influenza A virus (H1N1) and influenza B virus (Victoria lineage) were injected subcutaneously into naïve cynomolgus macaques twice. The whole virus particle vaccines induced higher titers of neutralizing antibodies against H1N1 influenza A virus and influenza B virus in the plasma of macaques than did the split vaccines. At challenge with H1N1 influenza A virus or influenza B virus, the virus titers in nasal swabs and the increases in body temperatures were lower in the macaques immunized with the whole virus particle vaccine than in those immunized with the split vaccine. Repertoire analyses of immunoglobulin heavy chain genes demonstrated that the number of B-lymphocyte subclones was increased in macaques after the 1st vaccination with the whole virus particle vaccine, but not with the split vaccine, indicating that the whole virus particle vaccine induced the activation of vaccine antigen-specific B-lymphocytes more vigorously than did the split vaccine at priming. Thus, the present findings suggest that the superior antibody induction ability of the whole virus particle vaccine as compared to the split vaccine is attributable to its stimulatory properties on the subclonal differentiation of antigen-specific B-lymphocytes.